Addition of bone morphogenetic protein type 2 to ascorbate and β-glycerophosphate supplementation did not enhance osteogenic differentiation of human adipose-derived stem cells - Ariadne Cristiane Cabral Cruz; Mariana Lúcia Silva; Thiago Caon; Cláudia Maria Oliveira Simões (Journal of Applied Oral Science, 2012)
Bone morphogenetic protein type 2 (BMP-2) is a potent local factor, which promotes bone formation and has been used as an osteogenic supplement for mesenchymal stem cells. OBJECTIVES: This study evaluated the effect of a recombinant BMP-2 as well as the endogenous BMP-4 and BMP-7 in the osteogenic differentiation of adipose-derived stem cells (ASCs) in medium supplemented with ascorbate and β-glycerophosphate. MATERIAL AND METHODS: Human ASCs were treated with osteogenic medium in the presence (ASCs+OM+BMP-2) or absence (ASCs+OM) of BMP-2. The alkaline phosphatase (ALP) activity was determined and the extracellular matrix mineralization was evaluated by Von Kossa staining and calcium quantification. The expressions of BMP-4, BMP-7, Smad1, Smad4, and phosphorylated Smad1/5/8 were analyzed by western blotting. Relative mRNA expressions of Smad1, BMP receptor type II (BMPR-II), osteonectin, and osteocalcin were evaluated by qPCR. Results: ASCs+OM demonstrated the highest expression of BMP-4 and BMP-7 at days 21 and 7, respectively, the highest levels of BMPR-II mRNA expression at day 28, and the highest levels of Smad1 mRNA at days 14 and 28. ASCs+OM+BMP-2 demonstrated the highest levels of Smad1 mRNA expression at days 1, 7, and 21, the highest expression of Smad1 at day 7, the highest expression of Smad4 at day 14, the highest ALP activity at days 14 and 21, and expression of phosphorylated Smad1/5/8 at day 7. ASCs+OM and ASCs+OM+BMP2 showed similar ALP activity at days 7 and 28, similar osteonectin and osteocalcin mRNA expression at all time periods, and similar calcium depositions at all time periods. CONCLUSIONS: We concluded that human ASCs expressed endogenous BMP-4 and BMP-7. Moreover, the supplementation of ASCs with BMP-2 did not increase the level of osteogenic markers in the initial (ALP activity), intermediate (osteonectin and osteocalcin), or final (calcium deposition) phases, suggesting that the exogenous addition of BMP-2 did not improve the in vitro osteogenesis process of human ASCs.